Effects of long‐term treatment on brain volume in patients with obstructive sleep apnea syndrome. Issue 1 (27th October 2015) - Kim, Hosung; Joo, EunYeon; Suh, Sooyeon; Kim, Jae‐Hun; Kim, Sung Tae; Hong, Seung Bong
Abstract: We assessed structural brain damage in obstructive sleep apnea syndrome (OSA) patients (21 males) and the effects of long‐term continuous positive airway pressure (CPAP) treatment (18.2 ± 12.4 months; 8–44 months) on brain structures and investigated the relationship between severity of OSA and effects of treatment. Using deformation‐based morphometry to measure local volume changes, we identified widespread neocortical and cerebellar atrophy in untreated patients compared to controls (59 males; Cohen's D  = 0.6; FDR < 0.05). Analysis of longitudinally scanned magnetic resonance imaging (MRI) scans both before and after treatment showed increased brain volume following treatment (FDR < 0.05). Volume increase was correlated with longer treatment in the cortical areas that largely overlapped with the initial atrophy. The areas overlying the hippocampal dentate gyrus and the cerebellar dentate nucleus displayed a volume increase after treatment. Patients with very severe OSA (AHI > 64) presented with prefrontal atrophy and displayed an additional volume increase in this area following treatment. Higher impairment of working memory in patients prior to treatment correlated with prefrontal volume increase after treatment. The large overlap between the initial brain damage and the extent of recovery after treatment suggests partial recovery of nonpermanent structural damage. Volume increases in the dentate gyrus and the dentate nucleus possibly likely indicate compensatory neurogenesis in response to diminishing oxidative stress. Such changes in other brain structures may explain gliosis, dendritic volume increase, or inflammation. This study provides neuroimaging evidence that revealed the positive effects of long‐term CPAP treatment in patients with OSA. Hum Brain Mapp 37:395–409, 2016 . ©2015 Wiley Periodicals, Inc.